Association between bystander cardiopulmonary resuscitation and redeemed prescriptions for antidepressants and anxiolytics in out-of-hospital cardiac arrest survivors. (June 2017) - Bundgaard, Kristian; Hansen, Steen M.; Mortensen, Rikke Nørmark; Wissenberg, Mads; Hansen, Malta; Lippert, Freddy; Gislason, Gunnar; Køber, Lars; Nielsen, Jimmi; Torp-Pedersen, Christian; Rasmussen, Bodil Steen; Kragholm, Kristian
Abstract: Aim: This study aimed to examine rates of redeemed prescriptions of antidepressants and anxiolytics, used as markers for cerebral dysfunction in out-of-hospital cardiac arrest (OHCA) survivors, and examine the association between bystander CPR and these psychoactive drugs. Methods: We included all 30-day survivors of OHCA in Denmark between 2001 and 2011, who had not redeemed prescriptions for antidepressants or anxiolytics in the last six months prior to OHCA. Main outcome measures were redeemed prescriptions of antidepressants and anxiolytics within one year after OHCA. Results: Among 2, 001 30-day survivors, 174 (8.6% died and 12.0% redeemed a first prescription for an antidepressant and 8.2% for an anxiolytic drug within one year after arrest. The corresponding frequencies for redeemed prescribed drugs among age- and sex-matched population controls were 7.5% and 5.2%, respectively. Among survivors who received bystander CPR, prescriptions for antidepressants and anxiolytics were redeemed in 11.1% [95% CI 9.2–13.3%] and 6.3% [95% CI 4.9–8.0%] of the cases, respectively, versus 17.2% [95% CI 13.9–21.1%] and 13.4% [95% CI 10.5–17.0%], respectively, among patients who had not received bystander CPR. Adjusted for age, sex, year of arrest, comorbidity, witnessed status and socioeconomic status, bystander CPR was associated with significant reductions in redeemed prescriptions for antidepressants, Hazard Ratio (HR) 0.71 [95% CI 0.52–0.98], P  = 0.031; and anxiolytics, HR 0.55 [95% CI 0.38–0.81], P  = 0.002. Conclusion: Relative to no bystander CPR, redeemed prescriptions for antidepressants and anxiolytics were significantly lower among 30-day survivors of OHCA who received bystander CPR, suggesting a cerebral dysfunction-lowering potential of bystander CPR.